2003
DOI: 10.1155/s1023621x03000320
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Eddy Simulation of Unsteady Flow in a Mixed‐Flow Pump

Abstract: This article describes the large-eddy simulation (LES) of the internal flows of a high–specific-speed, mixed-flow pump at low flow-rate ratios over which measured head-flow characteristics exhibit weak instability. In order to deal with a moving boundary interface in the flow field, a form of the finite-element method in which overset grids are applied from multiple dynamic frames of reference has been developed. The method is implemented as a parallel program by applying a domain-decomposition programming mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Unfortunately, although DNS gives the most precise results, the computational time is prohibitive for practical applications. The prevailing route to simulate time dependent flows is the LES method (Nobuhiro et al, 2003;Kato et al, 2003;Ji et al, 2013) proposed by Smagorinski (1963). Typically, LES resolves all the dynamically important scales of motion and a significant portion of the inertial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although DNS gives the most precise results, the computational time is prohibitive for practical applications. The prevailing route to simulate time dependent flows is the LES method (Nobuhiro et al, 2003;Kato et al, 2003;Ji et al, 2013) proposed by Smagorinski (1963). Typically, LES resolves all the dynamically important scales of motion and a significant portion of the inertial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between CFD and experimental results may be attributed to the grid resolution around the blade surface, and the current mesh resolution may be insufficient to resolve the turbulent boundary layer developing on the blade surface. Furthermore, effects of the leakage flow through the clearance are not considered in the present numerical simulation [15]. However, it can be found that the tendency of CFD results has a good agreement with the test results.…”
Section: Validation Of the Numerical Methodsmentioning
confidence: 95%
“…By neglecting the incompressible effect of the fluid, LES governing equations [15] to [17] can be described in the following form.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] study the flow characteristics of the unsteady and unstable flow using LES subgrid turbulence model. Abroad Kato [2] study the unsteady flow characteristics of mixed flow pump under off-designed condition based on LES sub-grid turbulence model. Miorini, et.al.…”
Section: Introductionmentioning
confidence: 99%